Removal of ciprofloxacin from aqueous solution using humic acid- and levulinic acid- coated Fe3O4 nanoparticles - KERKEZ KUYUMCU, ÖZGE (INST CHEMICAL ENGINEERS, 2017)
Humic acid (HA)- and levulinic acid (LA)-coated magnetic Fe3O4 nanoparticles were prepared and subsequently characterized using scanning electron microscopy, X-ray diffraction spectroscopy, Fourier transformer infrared spectroscopy, thermogravimetric analysis, particle size distribution analysis, and zeta-potential analysis. These magnetic nanoparticles were used for ciprofloxacin adsorption from aqueous solutions. Non-linear Langmuir and Freundlich adsorption isotherm models were used to explain the adsorption equilibria. The Langmuir adsorption capacities (q(m)) were 101.93 mg/g for HA-coated Fe3O4 and 53.76 mg/g for LA-coated Fe3O4. The appropriate contact times were 40 min for HA-coated Fe3O4 and 60 min for LA-coated Fe3O4. The adsorption rates and mechanisms were determined using pseudo-first-order and pseudo-second-order kinetic models. After the adsorption studies, the loaded nanoparticles were used for desorption studies, and their desorption kinetics were investigated. (C) 2017 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Humic acid-coated Fe3O4; Levulinic acid-coated Fe3O4; Ciprofloxacin; Adsorption; METAL-ORGANIC FRAMEWORK; MAGNETIC NANOPARTICLES; DRUG-DELIVERY; SURFACE MODIFICATION; MESOPOROUS CARBON; ADSORPTION; MECHANISMS; WATER